Gastroesophageal Reflux Risk Factor Analysis at Saiful Anwar Hospital in Malang - Tarigan, Ricky C; Pratomo, Bogi (Jurnal Penyakit Dalam Indonesia, 2019)
Introduction. Gastroesophageal reflux disease (GERD) is a pathological condition as a result of reflux of stomach contents into the esophagus with various symptoms that arise due to the involvement of the esophagus, larynx, and airways. The prevalence of GERD has increased lately. In Indonesia, 22.8% cases of esophagitis were reported. Analysis of the risk factors for GERD is very important in reducing the prevalence of GERD. This study aimed to identify the most influential risk factors for GERD patients so that it could become a reference to reduce the prevalence of GERD in the following year. Methods. This study was a cross-sectional study where data was taken based on data from medical records of patients undergoing the endoscopic procedure in the division of Hepatology Gastroenterology at Saiful Anwar Hospital Malang during 2016. The diagnosis was obtained from history, physical examination, and GERD diagnostic criteria from endoscopy according to the Los Angeles criteria. Results. Among 57 patients, there were 20 female (32.5%) and 37 male (67.5%), 63.16% of them are >40 years old. This study found that 28 patients (49.12%) consumed herbs, 31 patients (54.38%) found smoking, and those who consumed alcohol were 18 patients (31.48%). The analysis showed that factors related to the incidence of GERD were herbal consumption (p=0.007; OR 4.586 (95% CI: 95%: 1.386-15.177)) and alcohol consumption (p 0.027; OR 4.846 (95% CI: 1.024-22.929)). Conclusion. Consumption of herbal and alcohol appear to be risk factors of the incidence of GERD in this study.